Coal and Gangue Underground Pneumatic Separation Effect Evaluation Influenced by Different Airflow Directions. (17th March 2016) - Zheng, Kehong; Du, Changlong; Li, Jianping; Qiu, Bingjing
Abstract : Coal and gangue underground pneumatic separation is of key importance for green mining. Two kinds of arrangement schemes for high-pressure value used in pneumatic separation system are proposed in this study. Pneumatic separation effects are examined under different arrangement of high-pressure value. Here, theoretical pneumatic separation distance formulas of mineral particles affected by different airflow directions are derived and validated by a series of numerical simulations and orthogonal experiments. In the following analysis, the effects of gangue diameter (d ), conveyor velocity (v 0 ), and the height difference between conveyor belt and air nozzle (h p ) are mainly considered. The numerical simulation and experimental results indicate that pneumatic separation effects under the condition ofu andv 0 being in the opposite direction will be better than that ofu andv 0 being in the same direction. The pneumatic separation distanceΔ S shows a decreasing trend with the increasing of the three factors. The study also shows that gangue diameter has the most significant influence on separation distance, followed by conveyor velocityv 0 and height differenceh p .